Dislocating women from philosophy: five strategies (2010)
The paper deals with the feminist critique of the philosophical canon, challenging the fact that there are (almost) no women included in it. In the first part, the author sets up questions helping to open the space for interrogating the current Euro-American philosophical canon, followed by the summary of the development and results of its feminist critique. In the main body of the text, the surveys of the history of philosophy and encyclopedias of philosophy available in the Czech language and used in the Czech universities as textbooks are analyzed with the aim of mapping out the strategies of dislocation of women from philosophy. In the last part, the main reasons for including women in the canon are explored together with some questions accompanying them.